N-acetylcysteine reduce the stress induced by cold storage of platelets: A potential way to extend shelf life of platelets. (April 2021) - Handigund, Mallikarjun; Kim, Jeong Tae; Bae, Tae Won; Lee, Jaehyeon; Cho, Yong Gon
Highlights: N -acetylcysteine (NAC) potentially protects platelet characteristics during cold storage for up to 10 days. NAC improves the in vivo recovery via regulation ROS, platelet activation, and sialic acid levels. Synergistic effect of cold storage and use of NAC enables possibility of PCs storage beyond 10 days. Abstract: The room temperature storage used for platelets worldwide leads to platelet storage lesion (PSL) and risk of bacterial growth, limiting platelet shelf life and safety in transfusion. Thus, there is a need for an alternative storage method that can serve as effective temperature storage for platelet concentrates (PCs). In the previous investigation, we have shown that N-acetylcysteine (NAC) is a potential candidate for an additive solution to retain platelet characteristics during cold storage for up to 5 days. However, the study partially describes the efficacy and has drawbacks to address. Here, we used the apheresis platelet product with 50 mM NAC and stored up to 10 days under refrigerated condition (4 ± 1 °C). Stored platelet concentrates were analyzed for critical parameters such as platelet activation, annexin V binding, sialic acid, reactive oxygen species (ROS), neuraminidase activity, and in vivo efficacy using Prkdc scid mice. Investigation observations revealed that PCs with NAC showed reduced platelet activation, annexin V binding, ROS production, and sialic acid levels. in vivo recovery of PCs showed similar recovery rates stored PCs irrespective of treatment or storage condition. However, on the tenth day after 24 h, recovery in room temperature stored concentrates was about 32 %, whereas in NAC treated refrigerated concentrates, it stands at 47 %. These observations indicate that NAC addition protects refrigerated concentrates during long-term storage retaining the platelet integrity. The study also suggests that extending PC storage beyond 10 days is practically accomplishable with efficacy similar to room temperature (RT) stored PCs.